The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/1415-52732015000400003
|View full text |Cite
|
Sign up to set email alerts
|

Nutrional status and dietary factors in cystic fibrosis patients with delta F508 mutation

Abstract: Objective To examine the association between nutritional status and dietary factors in children and adolescents with cystic fibrosis that are carriers of delta F508 mutation. Methods Cross-sectional study of cystic fibrosis children and adolescents. Nutritional status (body mass index percentile) and dietary intake (3-day diet records presented as a percentage of estimated energy requirement) were assessed. Results Thirty six patients (median of 8.6; interquartile range 6.8-12.5 years; 50% male). The Poisson r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Santos et al reported a total percentage of 75% Phe508del pathogenic variants in 36 CF patients; of which 27.7% were homozygous and 47.3% were heterozygous. 21 Similarly, homozygous and heterozygous Phe508del pathogenic variant rates were reported as 53 and 39%, respectively, in a study by Gangell et al analyzing 215 children diagnosed with CF. 12 MacKenzie et al reported 46.4% homozygous and 39.3% heterozygous Phe508del pathogenic variants among their patients reached several 26,000 in 2010 from the multicenter research that was conducted between 2000 and 2016 in collaboration with 110 CF institutions.…”
Section: Discussionmentioning
confidence: 88%
“…Santos et al reported a total percentage of 75% Phe508del pathogenic variants in 36 CF patients; of which 27.7% were homozygous and 47.3% were heterozygous. 21 Similarly, homozygous and heterozygous Phe508del pathogenic variant rates were reported as 53 and 39%, respectively, in a study by Gangell et al analyzing 215 children diagnosed with CF. 12 MacKenzie et al reported 46.4% homozygous and 39.3% heterozygous Phe508del pathogenic variants among their patients reached several 26,000 in 2010 from the multicenter research that was conducted between 2000 and 2016 in collaboration with 110 CF institutions.…”
Section: Discussionmentioning
confidence: 88%
“…Individuals homozygous for F508del typically present with earlier and more severe respiratory complications and have earlier mortality ( Johansen et al, 1991 ; De Braekeleer et al, 1997 a; Mackenzie et al, 2014 ; Keogh et al, 2018 ). Most F508del homozygotes have exocrine pancreatic insufficiency but the effect of this genotype on weight and body mass index is controversial ( Lanng et al, 1991 ; Santos and Steemburgo, 2015 ; Leung et al, 2020 ; Medza et al, 2021 ). Homozygotes for F508del also have impaired glucose tolerance and a higher risk of cystic fibrosis-related diabetes (CFRD) ( Hamdi et al, 1993 ; Street et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%